TANGGUNG JAWAB PELAKU USAHA TERHADAP PENJUALAN BARANG DAN/ATAU JASA DENGAN SISTEM PROMOSI - Diaratih, Anggie (Private Law Department, Faculty of Law, University of Jember, Indonesia, 2023)
Promotion is one of the methods to increase sales by business actors and has been proven by increasing public buying interest. There have been several cases where consumers were disadvantaged in the sale of goods and/or services with a promotional system that did not match what was promised. So it takes responsibility from business actors to create comfort for consumers. Included in the law that regulates the promotion of sales of goods and/or services has the aim of creating a sense of security and comfort for both business actors and consumers in buying and selling transactions. The research method used in this paper is a type of normative juridical research that focuses on the application of norms and rules that exist in positive law. The results of the research on the discussion of this thesis are, first, regulations governing the sale of goods and/or services with promotions are provisions contained in Law Number 8 of 1999 concerning Consumer Protection Article 8 paragraph (1) letter f, Article 10 letter d, and Article 13 paragraph (1) of Law Number 8 of 1999 concerning Consumer Protection. Second, the legal responsibility of business actors for sales carried out with promotions that harm consumer interests is regulated in Article 4 letter h and Article 7 letter g of Law Number 8 of 1999 concerning Consumer Protection, and business actors are considered to have defaulted, because consumers receive goods which is not in accordance with what was promised. Third, efforts to resolve disputes against consumer losses due to transactions based on the promotion of goods and/or services based on Article 45 of Law Number 8 of 1999 concerning Consumer Protection can be through 2 (two) ways, namely through the court route (litigation) and external channels. court (non- litigation). Keywords: Legal Responsibility, Sale of Goods and/or Services, Promotion